Combined whole-organ imaging at single-cell resolution and immunohistochemical analysis of prostate cancer and its liver and brain metastases - Taranda, Julian; Mathew, Grinu; Watrud, Kaitlin; El-Amine, Nour; Lee, Matthew F.; Elowsky, Corey; Bludova, Anastasiia; Escobar Avelar, Sintia; Nowak, Dawid G.; Wee, Tse-Luen; Wilkinson, John E.; Trotman, Lloyd C.; et al. (Cell reports, 2021)
Early steps of cancer initiation and metastasis, while critical for understanding disease mechanisms, are difficult to visualize and study. Here, we describe an approach to study the processes of initiation, progression, and metastasis of prostate cancer (PC) in a genetically engineered RapidCaP mouse model, which combines whole-organ imaging by serial two-photon tomography (STPT) and post hoc thick-section immunofluorescent (IF) analysis. STPT enables the detection of single tumor-initiating cells within the entire prostate, and consequent IF analysis reveals a transition from normal to transformed epithelial tissue and cell escape from the tumor focus. STPT imaging of the liver and brain reveal the distribution of multiple metastatic foci in the liver and an early-stage metastatic cell invasion in the brain. This imaging and data analysis pipeline can be readily applied to other mouse models of cancer, offering a highly versatile whole-organ platform to study in situ mechanisms of cancer initiation and progression.